Nano Online 2016
DOI: 10.1515/nano.11671_2014.8
|View full text |Cite
|
Sign up to set email alerts
|

NH3-treated WO3 as low-cost and efficient counter electrode for dye-sensitized solar cells

Abstract: A novel low-cost and efficient counter electrode (CE) was obtained by treating catalytic inert tungsten trioxide (WO 3 ) nanomaterial in NH 3 atmosphere at elevated temperatures. The formation of tungsten oxynitride from WO 3 after NH 3 treatment, as evidenced by X-ray photoelectron spectroscopy and X-ray diffraction, increases the catalytic activity of the CE. Correspondingly, the power conversion efficiency (PCE) of the DSC is significantly increased from 0.9% for pristine WO 3 CE to 5.9% for NH 3 -treated W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Li et al used NH 3 -treated WO 3 as a CE in a DSSC, and it delivered a PCE of 5.9%, which was comparable to the PCE of the cell with Pt as CE (6.0%). 36 Here, we observed that with WO 3 /FTO and WO 3−x /FTO as CEs in QDSCs the PCEs are higher at 2.1 and 3.66% compared to that obtained with Pt as the CE (1.69%) reiterating that other catalytic materials are better performers compared to Pt in QDSCs and thus contrasting the trends observed in DSSCs. With carbon soot as CE and TiO 2 /CdS as the photoanode, the authors in ref 15 reported a PCE of 1.16%, which is lower than the value obtained here with soot (2.95%).…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…Li et al used NH 3 -treated WO 3 as a CE in a DSSC, and it delivered a PCE of 5.9%, which was comparable to the PCE of the cell with Pt as CE (6.0%). 36 Here, we observed that with WO 3 /FTO and WO 3−x /FTO as CEs in QDSCs the PCEs are higher at 2.1 and 3.66% compared to that obtained with Pt as the CE (1.69%) reiterating that other catalytic materials are better performers compared to Pt in QDSCs and thus contrasting the trends observed in DSSCs. With carbon soot as CE and TiO 2 /CdS as the photoanode, the authors in ref 15 reported a PCE of 1.16%, which is lower than the value obtained here with soot (2.95%).…”
Section: ■ Results and Discussionmentioning
confidence: 60%